Penerapan model pembelajaran think talk write untuk meningkatkan keterampilan menulis laporan pada peserta didik kelas iv sekolah dasar - Arba Dewi Larasati; Jenny Indrastoeti Siti Poerwanti; Sukarno Sukarno; Suyoto Suyoto (Universitas Sebelas Maret, 2019)
Abstract. This study aims to improve the skills of writing interview reports through Think Talk Write Learning Model for fourth grade of SD N Serengan II No. 256 Surakarta Academic year 2018/2019. The technique of collecting data uses observation, tests, interviews and documentation. Test validity of data using content validity and technical triangulation. The data analysis technique used an interactive model consisting of data collection, reduction, presentation, and conclusion drawing.This study is a Classroom Action Research conducted in two cycles. The subjects of this study were teachers and students, which 31 students. The results showed that the pre-action class average value of 55.65 increased to 74.35 in first cycle, increasing again to 84.44 in second cycle. The number of students in pre-action who achieved KKM was 3 students (9.68%), in the second cycle as many as 20 students (64.52%), and experienced an increase again to as many as 26 students (82.26%) in the cycle II. Based on the results of the study, it was concluded that: through the Think Talk Write learning model can improve the skills of writing interview reports to fourth grade students of SD N Serengan II No. 256 Surakarta Academic Year 2018/2019.Keywords: Think Talk Write learning model, writing skills, Skills for writing report on interview results, Elementary School